Building Hoopes vision - Calkins, Tim; Riderman, Stephanie Laura (London : Kellogg School of Management, 2018)
Dr. Phillip Hoopes, a LASIK surgeon, is considering how to respond to discounting by his competitors. He had built a high-end practice with costly advanced technology, but discounters had recently entered the market and other high-end practices in the area were starting to offer deep promotions in an effort to compete.
Originally Published InCalkins, T., & Riderman, S. L. (2018). Building Hoopes Vision. Kellogg School of Management. Evanston, IL: Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hoopes, Phillip C; Competition -- Case studies; LASIK (Eye surgery) -- Prices -- Case studies